Vigencia de la «banda típica» de la provincia de Chumbivilcas, departamento de Cuzco, Perú - Cárdenas Coavoy, Hubert Ramiro (2018)
This text is an ethnographic and sound approach to the «banda típica» (traditional band), one of the traditional musical groups with the greatest presence in the festivities of the districts and peasant communities of the province of Chumbivilcas, department of Cuzco, Peru. It is a descriptive work that examines the places where the band participates, the manner of dressing of its members, its instrumental composition and organization, the subject of the musical themes they interpret and their characteristic toques, exemplified by sound files recorded during field work and stored on the Internet to accompany this article.The field work began in March 2015 and gathers information obtained through participant observation, informal conversations, as well as individual and group interviews with traditional and popular musicians in the framework of the anniversary of the province of Chumbivilcas, (June 21, district de Santo Tomás); festivity of the of the Virgin of the Nativity, (September 8, district of Santo Tomás) and festivity of the of the Señor Justo Juez de Patapampa, (day of «compadres”, peasant community of Pfuisa, district of Llusco). Among the main findings is that the typical band has managed to adapt to the vertiginous changes of time due to the close link that it keeps with the turupukllay or «game of bulls», custom that is celebrated in the main festivities of the province of Chumbivilcas.